HUMAN SECURITY AND MIGRATORY WAVES: THE CURRENT BRAZILIAN CONTEXT - Calderaro, Malon Sousa; da Silva, André Ricardo Fonseca (Editora Impacto Científico, 2025)
This article examines the relationship between international migration, human security, and comprehensive protection policies, with a particular focus on Venezuelan migratory flows and the humanitarian response implemented by Brazil through Operation Welcome (Operação Acolhida). In light of the significant increase in migrants in recent years and the resulting social, economic, and humanitarian demands, the study seeks to assess whether the actions undertaken by the State, in partnership with civil society organizations, have been effective in promoting human security and ensuring basic rights for migrants. Using a qualitative approach based on documentary review and analysis of secondary data, the study concludes that Brazil’s response has made notable progress, especially in inter-institutional coordination and the provision of essential services, yet structural challenges persist, including social inclusion, access to formal employment, and the reduction of vulnerability. The findings highlight the need for integrated, long-term public policies capable of ensuring not only emergency assistance but also comprehensive and sustainable protection, recognizing migrants as rights holders and promoting their full social, economic, and cultural integration.DOI: https://doi.org/10.56238/edimpacto2025.084-021